0018 Simulation training incorporating a smartphone app increases foundation doctors' confidence in managing cardiac arrest. (2nd November 2015) - Thomas, Richard; Joyce, Aidan; Norman, Emma
Abstract : Background/context: Cardiac arrest demands prompt, effective treatment if the best possible outcomes are to be achieved. Previous research has demonstrated increased confidence and improved performance of skills following simulation based training. 1 A plethora of medical smartphone apps exist, but there is currently little evidence as to their clinical usefulness. Methodology: Pre- and post-intervention questionnaire to evaluate: (i) FY2s (n = 20) level of experience of cardiac arrests and (ii) their confidence in performing related clinical skills. (iii) The acceptability and usefulness of 'Resus Algorithms'; a smartphone app. Intervention: Two 90 min sessions of simulation training, using the smartphone app during scenarios as trainees felt appropriate. Results: 65% of respondents had attended less than 5 cardiac arrests. Following simulation training, confidence in using the defibrillator increased from 30% to 97.5% and confidence leading a cardiac arrest team increased from 5% to 67.5%. 93% found using a resus app helpful in training and 75% agreed they would consider using it at a cardiac arrest. Conclusions and recommendations: Simulation training increases Foundation Doctors' confidence in the skills required to manage cardiac arrest. FY2s consider a smartphone app to be a useful aid in the management of cardiac arrest. FY2s are more likely to use resuscitation smartphone apps if this is endorsed by senior clinician. Our results have provided us with the confidence to continue to invest and deliver simulation-based to FY doctors as part of their protected teaching programme. Reference: Knowles T, Rea B, Duke O, et al . Does deliberate practice with high fidelity simulation training improve the resuscitation technique of UK final year medical students? Resuscitation 2013;84 (S90):0300–9572